Advanced synchrotron-based and globar-sourced molecular (micro) spectroscopy contributions to advances in food and feed research on molecular structure, mycotoxin determination, and molecular nutrition. Issue 13 (2nd September 2018) - Shi, Haitao; Yu, Peiqiang
ABSTRACT: Mycotoxin contamination has been a worldwide problem for food and feeds production for a long time. There is an obviously increased focus of the food and feed industry toward the reduction of mycotoxin concentration in both the raw materials and finished products. Therefore, both effective qualitative and quantitative techniques for the determination of mycotoxins are required to minimize their harmful effects. Conventional wet chemical methods usually are time-consuming, expensive, and rely on complex extraction and cleanup pretreatments. Synchrotron-based and globar-based molecular spectroscopy have shown great potential to be developed as rapid and nondestructive tools for the determination of molecular structure, molecular nutrition and mycotoxins in feed and food. This article reviews the common types of mycotoxins in feed and food, their toxicity, as well as the conventional detection methods. The principle of advanced molecular spectroscopy techniques and their application prospects for mycotoxin detection are discussed. Recent progress in food and feed research with molecular spectroscopy techniques is highlighted. This review provides a potential and insight into how to determine the structure and mycotoxins of feed and food on a molecular basis with advanced Synchrotron-based and globar-based molecular (micro) spectroscopy.